2021
DOI: 10.3390/nu13114018
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Interventions for Patients with Melanoma: From Prevention to Therapy—An Update

Abstract: Melanoma is an aggressive skin cancer, whose incidence rates have increased over the past few decades. Risk factors for melanoma are both intrinsic (genetic and familiar predisposition) and extrinsic (environment, including sun exposure, and lifestyle). The recent advent of targeted and immune-based therapies has revolutionized the treatment of melanoma, and research is focusing on strategies to optimize them. Obesity is an established risk factor for several cancer types, but its possible role in the etiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 138 publications
(206 reference statements)
0
7
0
Order By: Relevance
“…Increased BMI has been revealed as a risk factor for skin melanoma. However, the link is not as strong as in other malignancies ( 51 , 52 ). In contrast, even a “obesity paradox” was disclosed for melanoma ( 51 ).…”
Section: Chronic Skin Conditions Influenced By Comorbid Obesitymentioning
confidence: 82%
See 1 more Smart Citation
“…Increased BMI has been revealed as a risk factor for skin melanoma. However, the link is not as strong as in other malignancies ( 51 , 52 ). In contrast, even a “obesity paradox” was disclosed for melanoma ( 51 ).…”
Section: Chronic Skin Conditions Influenced By Comorbid Obesitymentioning
confidence: 82%
“…However, the link is not as strong as in other malignancies (51,52). In contrast, even a "obesity paradox" was disclosed for melanoma (51). Gut microbiome modulation by diet could be the explanation and, possibly, the link between obesity and melanoma (53).…”
Section: Melanomamentioning
confidence: 92%
“…Indeed, energy intake was found not to be associated with CM in some studies [ 34 , 42 ] ( Table 4 ); in the study by Millen et al [ 38 ], the positive association (2021 kcal/day vs. 1,063 kcal/day: OR: 1.07, 95% CI: 0.68–1.69) was not statistically significant, whereas in our study, an increment of one SD in total energy intake was associated with a 67% increase in CM odds (OR: 1.67, 95% CI: 1.22–2.30). Higher energy intake is expected on average to lead to increased BMI, an index also associated with several cancer types, including CM [ 45 ]. Actually, two meta-analyses of observational studies [ 23 , 46 ] reported a positive association between increased BMI and CM in males, and our findings are in the same direction, showing a marginally non-significant positive association in males (OR: 1.59, 95% CI: 0.95–2.67, and in females, OR: 0.65, 95% CI: 0.32–1.30).…”
Section: Discussionmentioning
confidence: 99%
“…The patients with CMM are often diagnosed as advanced stage due to the inadequate attention, which is explained as one of the reasons for its poor prognosis and high mortality [ 19 ]. So due to the unsatisfaction of relatively poor diagnosis and prognosis of CMM, numerous studies on association between the related factors and the treatment of CMM have been receiving increasing attention [ 20 , 21 ]. Therefore, searching for these novel treatments are of great significance for CMM.…”
Section: Discussionmentioning
confidence: 99%